Autologous Fat Grafting for Mixed-Type Atrophic Acne Scars: A Case Report in Female - I Gusti Nyoman Darmaputra; Putu Akopita Devi (Glosains: Jurnal Sains Global Indonesia, 2026)
Background: Acne scars are a clinically prevalent and psychologically significant sequela of acne vulgaris, affecting up to 95% of patients and associated with reduced quality of life, social withdrawal, and diminished self-esteem. Despite decades of research, evidence for fat grafting in mixed-type atrophic acne scars remains limited to small case series. Objective: This case report aims to evaluate the short-term clinical outcomes of autologous fat grafting in a 37-year-old female with Goodman and Baron Grade IV mixed-type atrophic acne scars. Methods: This case study identified a 37-year-old female with atrophic acne scars. The tumescent technique was utilized to harvest fat from her abdomen, which was processed into microfat and nanofat using the Lipocube® NanoKit-5 and then injected subcutaneously and applied topically to the patient’s face. The efficacy of the procedures was assessed during different follow-up visits, with an emphasis on scar reduction and dermal regeneration. Results: A significant reduction in edema was clinically observed on Day 4 post-procedure. As this was a single case with a 4-day observation period, no statistical analysis was performed. Descriptive assessment tools were used at baseline and will be repeated at scheduled follow-up visits. Conclusion: Autologous fat transfer using microfat and nanofat is a promising preliminary therapy for atrophic acne scars. It provides cosmetic improvement with low morbidity. However, longer-term evaluation is needed to establish its efficacy. Future studies with larger cohorts and standardized multi-timepoint assessments are warranted to establish the role of this technique in standard dermatological practice.